EVALUASI KINERJA ANGKUTAN UMUM JENIS LYN DAN KEBIJAKAN PENANGANANNYA DI KABUPATEN SIDOARJO - Supriyatno, Dadang; Widayanti, Ari (Prosiding Forum Studi Transportasi Antar Perguruan Tinggi, 2015)
Public transport is extremely important to support the activities of the community. With the disaster in Sidoarjo in Lapindo mud, then it will have an impact on travel patterns and community activity going on. Performance of public transport services in Sidoarjo shows frequency of less well under the average of 6 vehicles/hour, headway/time between above average 10 minutes, under 70% load factor, the average speed is below 30 km/h as well as travel time travel an average of under 60 minutes. Low load factors will result in declining revenue vehicle operator implies welfare decline mainly on a lonely stretch of public transport passengers. Public transport service system should be based on a route in accordance with the Department of transportation on the route permit Sidoarjo. Things happen on the field about 20% of the routes serving the route does not match the permit number, and also some of the fleet does not operate, let alone the routes leading into the area because of declining passenger numbers Porong as a result of disastrous mud Lapindo. In this case the required public transport route network tailored to map the impact and development of Lapindo mud road network already and will be built in the area of Sidoarjo are tailored to the development of the region.